Differential effect of glucose ingestion on the neural processing of food stimuli in lean and overweight adults. Issue 3 (10th January 2013) - Heni, Martin; Kullmann, Stephanie; Ketterer, Caroline; Guthoff, Martina; Bayer, Margarete; Staiger, Harald; Machicao, Fausto; Häring, Hans‐Ulrich; Preissl, Hubert; Veit, Ralf; Fritsche, Andreas
<x xml:space="preserve">Abstract</x> Eating behavior is crucial in the development of obesity and Type 2 diabetes. To further investigate its regulation, we studied the effects of glucose versus water ingestion on the neural processing of visual high and low caloric food cues in 12 lean and 12 overweight subjects by functional magnetic resonance imaging. We found body weight to substantially impact the brain's response to visual food cues after glucose versus water ingestion. Specifically, there was a significant interaction between body weight, condition (water versus glucose), and caloric content of food cues. Although overweight subjects showed a generalized reduced response to food objects in the fusiform gyrus and precuneus, the lean group showed a differential pattern to high versus low caloric foods depending on glucose versus water ingestion. Furthermore, we observed plasma insulin and glucose associated effects. The hypothalamic response to high caloric food cues negatively correlated with changes in blood glucose 30 min after glucose ingestion, while especially brain regions in the prefrontal cortex showed a significant negative relationship with increases in plasma insulin 120 min after glucose ingestion. We conclude that the postprandial neural processing of food cues is highly influenced by body weight especially in visual areas, potentially altering visual attention to food. Furthermore, our results underline that insulin markedly influences prefrontal activity to high caloric food cues after a meal, indicating that postprandial hormones may be potential players in modulating executive control. Hum Brain Mapp 35:918–928, 2014. © 2013 Wiley Periodicals, Inc.